PERAN MUSIK TERHADAP PENINGKATAN KEMAMPUAN KOGNITIF ANAK HAMBATAN INTELEKTUAL RINGAN - Situmorang, Natasha Tiurma Putri; Tarjiah, Indina; Tarwiyah Adi Sam, Tuti (Program Studi Pendidikan Musik, 2023)
This study aims to obtain data on the role of music on the cognitive abilities of children with mild intellectual disabilities. Children with mild intellectual disabilities have intellectual characteristics which include: thinking skills that tend to be low, difficulty in paying attention and remembering things. So that they experience obstacles to work on and complete tasks related to mental and intellectual functions, lack of vocabulary, and lack of ability in abstract thinking. Therefore, a special way is needed to train the cognitive abilities of children with mild intellectual disabilities, namely with one type of art that is easier for children to accept and easier to learn, namely music.The research method used in this study is a literature review or the collection of library data obtained from Google Scholar who has a relationship and connection with the identified problem. Research analysis is done by collecting, analyzing and concluding the data obtained. The results of this study are music has an influence and plays an important role in improving the cognitive abilities of children with mild intellectual disabilities. Music can improve children's cognitive abilities with intellectual disabilities such as stimulating children's brain abilities with mild intellectual disabilities, training children's memory or brain memory, increasing brain intelligence, training language skills by remembering, understanding, and mastering vocabulary, influencing social and emotional development, training concentration and focus on children so that they can develop the potential that exists in children with mild intellectual disabilities.